Silicon-carbon negative electrode material and preparation method and negative electrode sheet, lithium ion battery

CN122907628APending Publication Date: 2026-10-13NOVUSILICON CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611383016.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0003]但现有技术仍面临以下瓶颈:1.微孔率不高:传统硬模板法的多孔碳制备依赖酸蚀模板(如HF刻蚀SiO2,其中HF是指氢氟酸,SiO2是指二氧化硅),不仅产生污染性废液,而且微孔率不高、孔隙连通性差(如CN119324206A所公开的内容)

Benefits of technology

本发明提出以酚醛树脂–煤沥青复合碳骨架作为沉积硅碳负极的基体,构建“协同成孔+增强相容+原位掺杂”三重创新路径,解决硅碳体系的结构与电化学耦合难题,具体如下:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907628A_ABST
    Figure CN122907628A_ABST
Patent Text Reader

Abstract

The application provides a phenolic coal-tar nitrogen-doped composite silicon-carbon negative electrode material and a preparation method and a negative electrode sheet and a lithium ion battery. The silicon-carbon negative electrode material comprises a composite carbon framework, a deposition phase and a carbon coating layer. The mass ratio of phenolic resin and coal-tar in the composite carbon framework is 2:1-1:4. The mass fraction of the composite carbon framework in the silicon-carbon negative electrode material is 30%-55wt%. The surface nitrogen element content is 0.2-0.6at%. The deposition phase is gas-phase deposition nano-silicon deposited on the surface of the composite carbon framework. The mass fraction of the gas-phase deposition nano-silicon in the silicon-carbon negative electrode material is 35%-60wt%. The gas-phase deposition nano-silicon is an amorphous silicon phase. The carbon coating layer is coated on the surface of the deposition phase. The thickness of the carbon coating layer is 2-8nm. The application realizes the synergistic improvement of mechanical strength, controllability of pore structure and interface chemical stability through molecular design and structure regulation, and provides a new path for the large-scale preparation of high-performance silicon-carbon negative electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery technology, and specifically relates to a phenolic-coal tar nitrogen-doped composite silicon-carbon anode material and its preparation method, as well as the anode sheet and lithium-ion battery. Background Technology

[0002] Lithium-ion batteries, with their high energy density, long cycle life, and environmental friendliness, have been widely used in consumer electronics, electric transportation, and large-scale energy storage. Silicon, as an anode material, is considered an ideal replacement for graphite due to its ultra-high theoretical specific capacity (approximately 4200 mAh / g). However, silicon experiences a volume expansion rate of up to approximately 300% during charge and discharge, accompanied by severe volumetric stress and irreversible structural damage. This process triggers a series of failure mechanisms, including continuous rupture and regeneration of the SEI film (solid electrolyte interphase), disruption of the conductive network, and pulverization of the electrode structure, severely limiting the practical application of silicon-based anodes. To alleviate these problems, researchers generally employ a "silicon-carbon composite" strategy, using a carbon matrix to buffer the volume changes of silicon, improve conductivity, and enhance the overall structural stability of the electrode.

[0003] However, existing technologies still face the following bottlenecks: 1. Low microporosity: Traditional hard template methods for porous carbon preparation rely on acid etching of the template (such as HF etching of SiO2, where HF refers to hydrofluoric acid and SiO2 refers to silicon dioxide), which not only generates polluting waste liquid but also results in low microporosity and poor pore connectivity (as disclosed in CN119324206A). 2. Fragile bonding: The thermal expansion coefficients of silicon and carbon matrix differ significantly, making interface cracking and active material loss prone to occur during cycling (as disclosed in CN116885126A). 3. Insufficient network: Nano-silicon is prone to agglomeration during deposition or cycling, blocking electron transport paths and leading to deterioration in low-temperature rate performance (as disclosed in CN118156450B). Summary of the Invention

[0004] This invention provides a phenolic-coal tar nitrogen-doped composite silicon-carbon anode material and its preparation method, as well as the anode sheet and lithium-ion battery. This invention achieves a synergistic improvement in mechanical strength, pore structure controllability and interfacial chemical stability through molecular design and structural regulation, providing a new path for the large-scale preparation of high-performance silicon-carbon anode materials.

[0005] To address the aforementioned technical problems, this invention provides a phenolic-coal tar nitrogen-doped composite silicon-carbon anode material, comprising: Composite carbon framework: phenolic resin and coal tar pitch in a mass ratio of 2:1–1:4, with micropores of 0.7–2.0 nm accounting for ≥78%, specific surface area ≥1600 m² / g, and total pore volume ≥0.6 cm³. 3 / g, the composite carbon framework has a mass fraction of 30%–55wt% in the silicon-carbon anode material, and its surface nitrogen content is 0.2–0.6at%; Deposited phase: The deposited phase is vapor-deposited nano-silicon deposited on the surface of the composite carbon framework; the mass fraction of this vapor-deposited nano-silicon in the silicon-carbon anode material is 35%–60wt%; this vapor-deposited nano-silicon is an amorphous silicon phase (a-Si); when X-ray powder diffraction (XRD) is performed using Cu-Kα rays, no obvious crystalline silicon diffraction peaks are observed in the diffraction angle range of 2θ = 28–56°. Among them, obvious crystalline silicon diffraction peaks refer to crystalline diffraction peaks with an aspect ratio greater than 3. Carbon coating: The carbon coating is applied to the surface of the deposited phase; the thickness of the carbon coating is 2–8 nm, and the mass fraction of the carbon coating in the silicon-carbon anode material is 1.0–5.5 wt%.

[0006] Preferably, the mass ratio of phenolic resin to coal tar pitch is 2:1 to 1:2.

[0007] Furthermore, the compressive strength of the silicon-carbon anode material satisfies the following condition: σ = 28.6 × P + 72.0, where σ is the compressive strength in MPa; and P is the mass fraction of phenolic resin in the composite carbon skeleton, ranging from 0.20 to 0.67.

[0008] The present invention also provides a method for preparing the phenolic-coal tar nitrogen-doped composite silicon-carbon anode material, the method comprising the following steps: S1. Phenolic resin and coal tar pitch are blended and granulated, and a pore-forming agent is added to obtain a composite precursor; S2. The composite precursor was activated with KOH and acid-washed to obtain a composite carbon framework; S3. The composite carbon framework is sequentially subjected to silane deposition and carbon source coating in a fluidized bed reactor; The pore-forming agent in S1 is 2–6 wt% of the total mass of phenolic resin and coal tar pitch; The activation conditions for KOH in S2 are: KOH to composite precursor mass ratio of 1:1–4:1, temperature of 700–1000℃, and time of 3–6 h. In step S3, the obtained composite carbon framework is heated to a first reaction temperature of 450–600°C under a protective atmosphere, and then silane gas is introduced for vapor deposition at a flow rate of 15 L / min–35 L / min for a deposition time of 5–15 h. After deposition, the temperature is raised to a second reaction temperature of 500–700°C, and then olefin gas is introduced for carbon source coating at a flow rate of 2 L / min–10 L / min for a coating time of 2–6 h.

[0009] Preferably, the mass of the pore-forming agent is 3–5 wt% of the total mass of the phenolic resin and coal tar pitch.

[0010] Furthermore, the pore-forming agent in S1 is at least one of NH4Cl, urea, melamine, and polydopamine; The protective atmosphere in S3 is at least one of nitrogen and argon, the silane gas is at least one of silane, silane and propane, and the olefin gas is at least one of acetylene, propylene, methane and ethylene.

[0011] Furthermore, the compaction density of the silicon-carbon anode material is 0.7–1.5 g / cm³. 3 .

[0012] Furthermore, the silicon-carbon anode material has a compaction density of 1.1 g / cm³. 3 The resistivity of the powder is <4.5Ω·cm.

[0013] Furthermore, the tap density of the silicon-carbon anode material is 0.7–1.2 g / cm³. 3 .

[0014] Furthermore, the D50 of the silicon-carbon anode material is 4–13 μm, and it meets the following conditions. That is, the particle size distribution span (D90-D10) / D50 of the silicon-carbon anode material satisfies 0.8 ≤ (D90-D10) / D50 ≤ 1.1.

[0015] The present invention also provides a negative electrode sheet, which includes a negative electrode current collector and a negative electrode coating coated on at least one side of the negative electrode current collector, wherein the negative electrode coating includes the silicon-carbon negative electrode material.

[0016] The present invention also provides a lithium-ion battery, which includes the aforementioned negative electrode sheet; the lithium-ion battery is any one of a liquid lithium-ion battery, a semi-solid lithium-ion battery, and an all-solid lithium-ion battery.

[0017] The beneficial effects of this invention are: This invention proposes using a phenolic resin-coal tar composite carbon framework as the matrix for depositing silicon-carbon anodes, constructing a triple innovative approach of "synergistic pore formation + enhanced compatibility + in-situ doping" to solve the structural and electrochemical coupling problem of silicon-carbon systems, as detailed below: (1) Synergistic pore-forming mechanism: Phenolic resin pyrolysis and the release of gas from the pore-forming agent form micropores. Coal tar pitch melts and rearranges at high temperature, filling and expanding the channels, ultimately constructing micropores with a size distribution of 0.7–2 nm and mesopores of 2–4 nm. This structure combines high specific surface area and continuous channels, which helps to improve electrolyte wettability and ion diffusion kinetics, while maintaining the compressive strength of the carbon skeleton. (2) Enhanced interfacial compatibility: The phenolic cross-linking network significantly improves the carbonization yield of coal tar pitch, forming a dense and continuous composite skeleton, which improves the compressive strength of the material and effectively buffers the stress concentration caused by silicon expansion. (3) In-situ nitrogen doping: The nitrogen-containing groups in the phenolic resin and pore-forming agent molecules are converted into stable C–N bonds at high temperature. This structure can induce uniform deposition of silicon precursors, while enhancing the wettability of the electrode / electrolyte interface and improving the electrochemical activity and cycle stability of silicon.

[0018] In summary, this invention achieves a synergistic improvement in mechanical strength, pore structure controllability, and interfacial chemical stability through molecular design and structural regulation, providing a new path for the large-scale preparation of high-performance silicon-carbon anode materials.

[0019] This invention achieves high specific surface area, excellent framework strength, and interface stability by synergistically controlling the carbon framework pore structure, nitrogen doping content, and carbon coating, significantly improving the initial efficiency, rate performance, and cycle life of silicon-carbon anodes. Its technical advantages lie in its controllable structure, stable performance, and low cycle decay, making it suitable for high-performance lithium-ion battery applications.

[0020] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description

[0021] Figure 1 This is a pore size distribution diagram of the composite carbon skeleton in Embodiment 1 of the present invention. Detailed Implementation

[0022] The following specific embodiments illustrate the detailed implementation of the present invention. Those skilled in the art can easily understand the advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented in other different ways; that is, different modifications and changes can be made without departing from the scope disclosed in the present invention. The term "an embodiment" or "embodiment" as used herein refers to a specific feature, structure, or property included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not refer to the same embodiment, nor does it exclude other embodiments.

[0023] Example: A phenolic-coal tar nitrogen-doped composite silicon-carbon anode material, the silicon-carbon anode material comprising: Composite carbon framework: phenolic resin and coal tar pitch in a mass ratio of 2:1–1:4, with micropores of 0.7–2.0 nm accounting for ≥78%, specific surface area ≥1600 m² / g, and total pore volume ≥0.6 cm³. 3 / g, the composite carbon framework has a mass fraction of 30%–55wt% in the silicon-carbon anode material, and its surface nitrogen content is 0.2–0.6at%; Deposited phase: The deposited phase is vapor-deposited nano-silicon deposited on the surface of the composite carbon framework; the mass fraction of this vapor-deposited nano-silicon in the silicon-carbon anode material is 35%–60wt%; this vapor-deposited nano-silicon is an amorphous silicon phase; when X-ray powder diffraction test is performed using Cu-Kα rays, no obvious crystalline silicon diffraction peaks are observed in the diffraction angle range of 2θ = 28–56°. Among them, obvious crystalline silicon diffraction peaks refer to crystalline diffraction peaks with an aspect ratio greater than 3. Carbon coating: The carbon coating is applied to the surface of the deposited phase; the thickness of the carbon coating is 2–8 nm, and the mass fraction of the carbon coating in the silicon-carbon anode material is 1.0–5.5 wt%.

[0024] The compressive strength of the silicon-carbon anode material satisfies the following condition: σ = 28.6 × P + 72.0, where σ is the compressive strength in MPa; P is the mass fraction of phenolic resin in the composite carbon skeleton, ranging from 0.20 to 0.67.

[0025] The preparation method of silicon-carbon anode material and the preparation method of the battery used for testing are described in detail using Example 1 as an example.

[0026] Example 1

[0027] 1. Preparation method of phenolic-coal tar nitrogen-doped composite silicon-carbon anode material: S1. 150 kg of phenolic resin powder with a particle size of approximately 5 μm and 100 kg of coal tar pitch were mixed at a mass ratio of 1.5:1 and thoroughly mixed in a planetary ball mill. During the ball milling process, 4 wt% urea (4 wt% of the total mass of phenolic resin and coal tar pitch) was added, serving as both a pore-forming agent and a nitrogen-doping precursor. The urea decomposes during the subsequent heat treatment stage, releasing gas to form a porous structure and simultaneously providing a nitrogen source for the composite carbon framework. The resulting precursor particles, after uniform mixing, have a uniform particle size, which is beneficial for the homogeneity of subsequent activation reactions. The final composite precursor is obtained.

[0028] S2. The composite precursor was mixed with potassium hydroxide (KOH) at a mass ratio of 3:1 and impregnated. After drying, it was heated to 800℃ under a nitrogen atmosphere and held at that temperature for 4 h to complete activation. After cooling, residual inorganic salts were removed by acid washing, followed by repeated washing with deionized water until neutral. Finally, it was vacuum dried at 80℃ to obtain the composite carbon framework. The nitrogen atom ratio on the surface of the composite carbon framework was analyzed using XPS.

[0029] S3. The nitrogen-doped composite carbon framework was placed in a fluidized bed reactor for silane deposition. Silane was introduced at 500°C using nitrogen as a diluent gas, with a silane to nitrogen volumetric flow rate ratio of 6:1 and a flow rate of 20 L / min. The reaction lasted for 10 h, allowing silicon to be uniformly deposited inside the material's pores.

[0030] A silicon-supported composite framework was heated to 610 °C in a fluidized bed, then switched to an acetylene atmosphere at a flow rate of 5 L / min and maintained for 4 h, allowing the acetylene to decompose on the surface to form a carbon coating layer. The thickness of the carbon coating layer was characterized by TEM (transmission electron microscopy), and the thickness of the carbon coating layer obtained by this method was approximately 5 nm.

[0031] 2. Half-cell preparation method

[0032] Preparation of negative electrode sheet: The negative electrode sheet comprises a copper foil current collector and a negative electrode coating material applied to both sides of the copper foil. The silicon-carbon negative electrode material, single-walled carbon nanotubes (SWCNTs), conductive carbon black (Super P), sodium carboxymethyl cellulose (CMC), and polyacrylic acid (PAA) were mixed and dispersed in a deionized water medium in a slurry at a mass ratio of 95:1:1.5:1.5:1, resulting in a solid content of 45 wt%. The uniform and stable slurry was then evenly coated onto a 15 μm thick copper foil current collector and dried in a vacuum oven at 70°C for 10 hours to remove residual solvents and moisture, yielding a structurally stable, dry electrode sheet. Finally, the negative electrode sheet was cold-pressed and punched into circular pieces with a diameter of 14 mm and a compaction density of 0.8 g / cm³. 3 It serves as the negative electrode in lithium-ion battery assembly.

[0033] Button cell battery assembly method: A coin cell simulated battery was assembled in a glove box filled with high-purity argon gas (O2 and H2O content both <0.1 ppm). A lithium metal sheet was used as both the counter and reference electrode, and the negative electrode was a silicon-carbon composite material negative electrode. A 1 mol·L⁻¹ electrolyte was used. -¹ The LiPF6 solution is prepared by mixing ethylene carbonate (EC) and dimethyl carbonate (DMC) in a 1:1 volume ratio. A polypropylene microporous membrane (such as Celgard 2400, i.e., the 2400 type polypropylene microporous membrane manufactured by Celgard LLC) is placed between the positive and negative electrodes as a separator.

[0034] 3. Full cell preparation method

[0035] Method for manufacturing negative electrode plates: A negative electrode material with a solid content of 50 wt% was formed by stirring 96 wt% of the negative electrode active material (90 wt% graphite and 10 wt% of the aforementioned silicon-carbon negative electrode material), 1.5 wt% of conductive carbon black (Super P), 0.8 wt% of sodium carboxymethyl cellulose (CMC), 1.2 wt% of styrene-butadiene rubber (SBR), and 0.5 wt% of polyacrylic acid (PAA) in deionized water. This negative electrode material was coated onto both sides of a 15 μm copper foil, and after drying, cold pressing, slitting, and cutting, a negative electrode sheet was obtained. The areal density of the negative electrode sheet was 6 mg / cm³. 2 The compaction density of the negative electrode sheet is 1.5 g / cm³. 3 .

[0036] Method for manufacturing positive electrode sheets: Take the positive electrode active material (Li1Ni) 0.8 Co 0.1 Mn 0.1 O2, conductive carbon black (Super P), multi-walled carbon nanotubes (HCNT), and polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone (NMP) solvent system at a mass ratio of 96:1:1:2 to obtain a positive electrode coating material. This material was then coated onto a 12.0 μm thick aluminum foil, dried, and cold-pressed to obtain a positive electrode sheet with a compaction density of 3.5 g / cm³. 3 .

[0037] Electrolyte preparation: An electrolyte was prepared by mixing lithium hexafluorophosphate (LiPF6), ethylene carbonate (EC), dimethyl carbonate (DMC), fluoroethylene carbonate (FEC), ethylene sulfate (DTD), and vinylene carbonate (VC) in a mass percentage ratio of 11.5: 21.6: 52.1: 2.95: 6.88: 4.92, with a LiPF6 concentration of 1 mol / L.

[0038] Selection of diaphragm: A high-porosity membrane was selected, in which the thickness of the PE (polyethylene) base membrane is 9μm, the thickness of the ceramic coating on both sides of the base membrane is 1.0μm, and the porosity is 40.5%.

[0039] Assembly method for a full battery: Nine negative electrode sheets and eight positive electrode sheets were Z-shaped stacked, and aluminum tabs (positive electrode) and nickel tabs (negative electrode) were welded on respectively. The cell was sequentially hot-pressed at 80 ℃ for 1 min and cold-pressed at room temperature for 1 min, then die-stamped with a 3 mm die, and finally top-sealed and side-sealed at 190 ℃ for 6 s. The resulting cell was baked in a vacuum nitrogen atmosphere at 95 ℃ for 24 h, with moisture content controlled below 200 ppm. Subsequently, the above-mentioned electrolyte was injected, and the cell was heat-sealed at 190 ℃ for 3 s at –90 kPa, and finally immersed at 45 ℃ for 48 h to obtain a stable assembled battery.

[0040] Example 2

[0041] The difference between this embodiment and Embodiment 1 is that the mass ratio of 200 kg of phenolic resin powder and 100 kg of coal tar pitch added during the preparation of the phenolic-coal tar pitch nitrogen-doped composite carbon skeleton is 2:1. All other aspects are the same as in Embodiment 1.

[0042] Example 3

[0043] The difference between this embodiment and Embodiment 1 is that the mass ratio of 180 kg of phenolic resin powder and 100 kg of coal tar pitch added during the preparation of the phenolic-coal tar pitch nitrogen-doped composite carbon skeleton is 1.8:1. All other aspects are the same as in Embodiment 1.

[0044] Example 4

[0045] The difference between this embodiment and Embodiment 1 is that the mass ratio of 120 kg of phenolic resin powder and 100 kg of coal tar pitch added during the preparation of the phenolic-coal tar pitch nitrogen-doped composite carbon skeleton is 1.2:1. All other aspects are the same as in Embodiment 1.

[0046] Example 5

[0047] The difference between this embodiment and Embodiment 1 is that the mass ratio of 100 kg of phenolic resin powder and 100 kg of coal tar pitch added during the preparation of the phenolic-coal tar pitch nitrogen-doped composite carbon skeleton is 1:1. All other aspects are the same as in Embodiment 1.

[0048] Example 6

[0049] The difference between this embodiment and Embodiment 1 is that the urea added during the preparation of the phenolic-coal tar nitrogen-doped composite carbon skeleton accounts for 2 wt% of the total mass of phenolic resin and coal tar, while all other aspects are the same as in Embodiment 1.

[0050] Example 7

[0051] The difference between this embodiment and Embodiment 1 is that the urea added during the preparation of the phenolic-coal tar nitrogen-doped composite carbon skeleton accounts for 3 wt% of the total mass of phenolic resin and coal tar, while all other aspects are the same as in Embodiment 1.

[0052] Example 8

[0053] The difference between this embodiment and Embodiment 1 is that the urea added during the preparation of the phenolic-coal tar nitrogen-doped composite carbon skeleton accounts for 5 wt% of the total mass of phenolic resin and coal tar, while all other aspects are the same as in Embodiment 1.

[0054] Example 9

[0055] The difference between this embodiment and Embodiment 1 is that the urea added during the preparation of the phenolic-coal tar nitrogen-doped composite carbon skeleton accounts for 6 wt% of the total mass of phenolic resin and coal tar, while all other aspects are the same as in Embodiment 1.

[0056] Example 10

[0057] The difference between this embodiment and Embodiment 1 is that the mass ratio of KOH to the composite precursor is 1:1 during the activation of the composite carbon framework; all other aspects are the same as in Embodiment 1.

[0058] Example 11

[0059] The difference between this embodiment and Embodiment 1 is that the mass ratio of KOH to the composite precursor is 2:1 during the activation of the composite carbon framework; all other aspects are the same as in Embodiment 1.

[0060] Example 12

[0061] The difference between this embodiment and Example 1 is that the mass ratio of KOH to the composite precursor is 3.5:1 during the activation of the composite carbon framework; all other aspects are the same as in Example 1.

[0062] Example 13

[0063] The difference between this embodiment and Embodiment 1 is that the mass ratio of KOH to the composite precursor during the activation process of the composite carbon framework is 4.0:1, while all other aspects are the same as in Embodiment 1.

[0064] Example 14

[0065] The difference between this embodiment and Embodiment 1 is that the silane deposition time in the fluidized bed reactor is 5 h, while all other aspects are the same as in Embodiment 1.

[0066] Example 15

[0067] The difference between this embodiment and Embodiment 1 is that the silane deposition time in the fluidized bed reactor is 7.5 h, while all other aspects are the same as in Embodiment 1.

[0068] Example 16

[0069] The difference between this embodiment and Embodiment 1 is that the silane deposition time in the fluidized bed reactor is 12.5 h, while all other aspects are the same as in Embodiment 1.

[0070] Example 17

[0071] The difference between this embodiment and Embodiment 1 is that the silane deposition time in the fluidized bed reactor is 15 h, while all other aspects are the same as in Embodiment 1.

[0072] Example 18

[0073] The difference between this embodiment and Embodiment 1 is that the carbon coating time for silicon-carbon deposition in the fluidized bed is 2 hours (the carbon coating layer thickness is 2 nm), while all other aspects are the same as in Embodiment 1.

[0074] Example 19

[0075] The difference between this embodiment and Embodiment 1 is that the carbon coating time for silicon-carbon deposition in the fluidized bed is 5 hours (the carbon coating layer thickness is 6.5 nm), while all other aspects are the same as in Embodiment 1.

[0076] Example 20

[0077] The difference between this embodiment and Embodiment 1 is that the carbon coating time for silicon-carbon deposition in the fluidized bed is 6 hours (the carbon coating layer thickness is 8.0 nm), while all other aspects are the same as in Embodiment 1.

[0078] Comparative Example 1

[0079] The difference between this comparative example and Example 1 is that only coal tar pitch is added during the preparation of the carbon skeleton, and no phenolic resin is added. Everything else is the same as in Example 1.

[0080] Comparative Example 2

[0081] The difference between this comparative example and Example 1 is that no pore-forming agent is added during the preparation of the phenolic-coal tar nitrogen-doped composite carbon skeleton; otherwise, they are the same as in Example 1.

[0082] The following are the testing methods for the relevant performance indicators.

[0083] 1. Characterization methods for composite carbon framework structures: The pore structure of the composite carbon framework was characterized using the nitrogen adsorption-desorption method. Dry samples were placed in a surface area analyzer and degassed at 200–300 °C for 6–12 hours under high vacuum to remove surface impurities. Nitrogen adsorption-desorption isotherms were then measured at 77 K liquid nitrogen. Specific surface area was calculated using the BET (Brunor-Emmett-Taylor) method within the relative pressure range of P / P0 = 0.05–0.3. Total pore volume was calculated from the adsorption amount at P / P0 ≈ 0.99. Pore size distribution was analyzed using the t-plot (adsorption layer thickness curve method) or Horvath-Kawazoe method for micropores (<2 nm) and the BJH (Barrett-Joyner-Halenda) method for mesopores (2–50 nm). The pore structure type was determined based on the adsorption-desorption curves, ultimately yielding the specific surface area, pore volume, and pore size distribution of the material. The pore size distribution diagram of the composite carbon framework in Example 1 is shown below. Figure 1 As shown.

[0084] XRD (X-ray diffraction) measurement method: A copper target X-ray diffractometer (Cu-Kα radiation, 1.54 Å, tube voltage 40 kV, tube current 40 mA) was used. The sample was uniformly dispersed on a silicon substrate, and XRD patterns were acquired at a scanning rate of 2° / min in the range of 2θ = 15°-70°.

[0085] 2. Method for determining the nitrogen content on the surface of composite carbon framework: The nitrogen content on the surface of the composite carbon framework was determined using X-ray photoelectron spectroscopy (XPS). The dried, powdered sample was evenly spread on the sample stage and placed in a vacuum chamber (pressure approximately 10). -9 The sample was excited using monochromatic Al Kα X-rays (hν=1486.6eV), and the entire spectrum was scanned to obtain the elemental composition. The N 1s core energy spectrum was measured with high resolution. Different chemical states of nitrogen (such as pyridine nitrogen, pyrrole nitrogen, graphitic nitrogen, etc.) were distinguished by peak fitting. The proportion of nitrogen atoms on the sample surface (at%) was calculated by correcting the peak area with a sensitivity factor. At the same time, the C 1s (284.8eV) spectrum peak was recorded as a reference.

[0086] 3. Method for determining silicon content in silicon-carbon anode materials: Indirect determination using a carbon-sulfur analyzer: The sample powder is placed in the carbon-sulfur analyzer and completely burned at high temperature. The total carbon content is then measured, and the carbon content is subtracted from the total mass of the sample. The remainder is the silicon content.

[0087] 4. Methods for determining D10, D50, and D90 of silicon-carbon anode materials: The particle size of silicon-carbon particles in silicon-carbon anode materials was determined using a wet laser particle size analyzer. Particle size is inversely proportional to the angle of scattered light generated after laser irradiation; analysis of the intensity distribution of captured scattered light yields the particle size distribution in the sample. Approximately 0.5 g of sample was added to a suitable dispersion medium (such as deionized water or anhydrous ethanol) and sonicated for 5 minutes to ensure thorough and uniform particle dispersion. The suspension was slowly added to the sample cell to achieve the ideal light-blocking level, and scanning measurements were initiated to obtain the particle size distribution results.

[0088] 5. Method for determining the compressive strength of silicon-carbon anode materials: According to ASTM D695 standard, silicon-carbon anode material is pressed into a standard cylinder (Ø6mm×8mm) and compressed to the point of fracture in a universal testing machine at a rate of 0.5 mm / min. The compressive strength σ (σ = maximum load ÷ area under stress) is calculated. Multiple sets of samples can be repeatedly tested to obtain the average value and standard deviation, so as to comprehensively evaluate the mechanical properties of the deposited silicon-carbon material.

[0089] 6. Method for determining the resistivity of silicon-carbon anode material powder: According to GB / T 24521-2009 standard, 1.0g of silicon carbide powder is pressed into an 8mm mold at 10 MPa for 30s to form a cylindrical blank with a compacted density precisely controlled to 1.10±0.02 g / cm³. A constant current of 1.0 mA is applied using a four-probe resistance meter (such as Loresta-GP), the voltage drop is measured, and the resistivity is calculated (formula: ρ=(π·ΔV·t) / (I·ln2)). The test is repeated 5 times, and the average value is taken. Here, ρ is the resistivity, usually expressed in Ω. cm or Ω m; ΔV is the potential difference (or voltage drop) between the two inner probes; I is the constant current flowing through the two outer probes; π and ln2 are both geometric correction factors.

[0090] 7. Method for determining the tap density of silicon-carbon anode material powder: According to GB / T 5162-2021 / ISO 3953:2011 standard, take 10g of dry silicon-carbon anode material powder that has passed through a 100-mesh sieve, place it in the measuring cylinder of a 25cm³ tap density meter, vibrate it 2500 times at a frequency of 250±15 times / minute (amplitude 3.0mm), read the volume V after tapping, and calculate the tap density ρ=m / V. Repeat 3 times and take the average value.

[0091] 8. Button test method: The coin cell lithium battery was placed in a constant temperature chamber at 25°C for 6 hours, discharged at constant current and constant voltage at 0.1C to 5mV with a cutoff current of 0.01C, and left to stand for 30 minutes. Then it was charged at constant current and constant voltage at 0.1C to 1.5V with a cutoff current of 0.01C to obtain the first coulombic efficiency (referred to as "first efficiency") and charge-discharge curve.

[0092] 9. Full battery rate performance test method: After discharging the all-electric soft-pack lithium battery to 2.5V and placing it in a 25℃ constant temperature chamber for 6 hours, test it according to the following steps: (1) Under 1C conditions, constant current and constant voltage charging to 4.2V, cutoff current is 0.1C, and stand for 30 minutes. The capacity of constant current charging to 4.2V is Q1 (constant current segment capacity). (2) Discharge under constant current at 1C until 2.5V cutoff, with a cutoff current of 0.1C, and let stand for 30 minutes; (3) Under 6C conditions, constant current and constant voltage charging to 4.2V, the cutoff current is 0.1C, and it is left to stand for 30 minutes. The capacity meter that is constant current charged to 4.2V is Q6. (4) Discharge under constant current at 1C until 2.5V cutoff, with a cutoff current of 0.1C, and let stand for 30 minutes; The capacity retention rate of a lithium battery at 25℃ is calculated as: Q6 / Q1×100.

[0093] 10. Full battery cycle performance test method: Place the battery in a 25°C constant temperature chamber for 6 hours and test it according to the following steps: (1) First round of constant current and constant voltage charging: charge at a constant current of 0.1C to 4.2V, then switch to constant voltage charging until the current drops to 0.01C.

[0094] (2) Let it stand for 30 minutes after charging is complete.

[0095] (3) Perform constant current discharge, and discharge to 2.5V at a rate of 0.1C.

[0096] (4) Cyclic charge and discharge process: Charge at a constant current rate of 1C to 4.2V. Let stand for 30 minutes again. Discharge at a constant current rate of 1C to 2.5V.

[0097] (5) Repeat the above charging and discharging process for a total of 600 cycles.

[0098] Statistical analysis of battery discharge capacity Q after 1 cycle and 600 cycles cyc1 and Q cyc600 Calculate the battery capacity decay rate: (Q) cyc1 -Q cyc600 ) / Q cyc1×100.

[0099] Table 1

[0100] Comparing Examples 1 to 5 in Table 1, it can be seen that the ratio of phenolic resin to coal tar pitch is the core factor determining the pore structure, mechanical properties, and electrochemical performance of the composite carbon framework. When the phenolic resin ratio is too high (Examples 2 and 3), the framework density increases, and the compressive strength can reach over 90 MPa. Although this can effectively resist silicon volume expansion, it excessively inhibits pore structure development, causing the specific surface area and pore volume to drop to near the critical values ​​(1600–1750 m² / g, 0.6–0.8 cm³ / g). Ion diffusion is restricted, leading to a decrease in first-efficiency and rate performance. When the phenolic resin ratio is too low (Example 5), excessive melting and rearrangement of the coal tar pitch causes pore collapse and framework fragility, reducing the compressive strength to around 86 MPa. Capacity retention and cycle stability significantly decline. In contrast, Example 1 (phenolic resin: coal tar pitch = 1.5:1) achieved the optimal balance: its micropore ratio reached 86.2%, with a specific surface area of ​​2050 m² / g and a pore volume of 0.95 cm³ / g, ensuring excellent electrolyte wettability and lithium-ion diffusion channels while maintaining high framework compressive strength, thus exhibiting the best first-efficiency, rate, and cycle performance. Mechanistically, this optimal ratio provides sufficient mechanical stability to the phenolic resin-crosslinked carbon framework, while the liquid-phase rearrangement of the coal tar pitch at high temperatures assists in the formation of interconnected channels. Furthermore, nitrogen atoms generated from urea decomposition participate in the doping of the carbon framework, ultimately achieving synergistic optimization in structural integrity, ion transport, and interfacial chemistry, thereby significantly improving the overall electrochemical performance of the silicon-carbon composite anode. As shown in Table 1, a mass ratio of phenolic resin to coal tar pitch of 2:1 to 1:2 is even more optimal.

[0101] Table 2

[0102] Comparing Examples 1, 6 to 9 in Table 2, it can be seen that the amount of urea added has a dual impact on the pore structure regulation and nitrogen doping level of the composite carbon framework, thus dominating the differences in electrochemical performance. Low addition (2 wt%) makes it difficult to form sufficient channels and effective nitrogen activation, leading to obstructed ion transport and uneven SEI film, resulting in lower first-efficiency and capacity retention. Excessive addition (≥5 wt%) causes channel collapse and increased surface defects, exacerbating side reactions and leading to performance degradation. In contrast, a moderate urea ratio (4 wt%) achieves a balance between pore structure development and nitrogen doping, taking into account ion diffusion channels, framework stability, and interfacial compatibility, resulting in optimal performance in terms of first-efficiency, rate retention, and cycle stability. This indicates that precise control of the urea addition is a key strategy for obtaining high-performance silicon-carbon anodes. As shown in Table 2, even better is a pore-forming agent mass of 3–5 wt% of the total mass of phenolic resin and coal tar pitch.

[0103] Table 3

[0104] Comparing Examples 10 to 13 in Table 3, it can be seen that the mass ratio of KOH to the composite precursor is another core factor determining the pore structure, specific surface area, pore volume, and electrochemical performance of the composite carbon framework. KOH activation etches micropores and expands the pore network within the carbon matrix by generating intermediate products such as potassium metal, K₂CO₃, and H₂ / CO / CO₂. Therefore, the amount of activator (KOH to composite precursor mass ratio) directly controls the etching intensity, pore wall thickness, and surface defect density. A KOH to composite precursor mass ratio of 1:1 indicates weak activation, resulting in insufficient etching and low micropore size and specific surface area (1655 m² / g, pore volume 0.67). The KOH / composite precursor ratio (cm³ / g) restricts electrolyte wetting and ion channels, resulting in poor kinetics despite fewer surface defects and reduced irreversible reactions, leading to lower 6C retention and moderate first-cycle efficiency. Increasing the KOH / composite precursor mass ratio to 2:1 results in more thorough etching, a significant increase in the proportion and volume of micropores, and improved ion / electrolyte permeability, thus enhancing rate performance. Further increasing to approximately 3–3.5:1 approaches the optimal etching-support balance: well-developed pore structure (high specific surface area and sufficient pore volume) and maintained carbon wall mechanical integrity achieve excellent ion diffusion, uniform silicon deposition, and stress buffering, resulting in higher first-cycle efficiency and better rate / cycle performance. However, when the KOH / composite precursor mass ratio is too high, etching becomes excessive, pore walls thin or partially collapse, pore connectivity is disrupted, and numerous surface defects are generated, leading to more irreversible side reactions, localized stress concentration, and ultimately a decrease in first-cycle efficiency and rate performance, accelerating long-term degradation. In summary, KOH activation exhibits a typical three-stage behavior of "etching-optimization-destruction": insufficient etching limits kinetics, moderate etching optimizes channels and mechanics, and excessive etching destroys the framework and increases side reactions, thus producing the performance fluctuations shown in the table.

[0105] Table 4

[0106] Comparing Examples 14 to 17 in Table 4, it can be seen that the silane deposition time plays a dominant role in the silicon loading and pore structure retention, thus determining the electrochemical performance. Insufficient deposition time (5 h) results in uneven silicon distribution and low filling capacity. Although some pores are retained, the activity is insufficient, leading to a significant reduction in initial efficiency and limited rate performance. Moderate deposition (7.5–10 h) allows for uniform silicon deposition within the pores while maintaining reasonable porosity and specific surface area, ensuring both high active capacity and favorable ion transport, thus achieving a balance between maximum initial efficiency and excellent cycle / rate performance. Excessive deposition (12.5–15 h) leads to partial pore blockage, a decrease in effective specific surface area, and hindered ion diffusion. Simultaneously, the increased silicon layer thickness causes uneven volume expansion and increased side reactions, resulting in decreased initial efficiency and rate performance, and accelerated cycle decay. Overall, the optimal silicon deposition time window is 7.5–10 h, which balances pore structure integrity and silicon loading uniformity.

[0107] Table 5

[0108] Comparing Examples 18 to 20 in Table 5, it can be seen that the carbon coating time (i.e., coating layer thickness) directly affects the interfacial stability, ion transport resistance, and degree of side reactions of silicon particles. Insufficient coating (2 h, 2 nm) results in a thin carbon layer that is difficult to form a continuous and dense buffer layer, leading to direct contact between silicon and the electrolyte, severe side reactions, low first-time efficiency, and poor cycle stability and rate performance. Moderate coating (4–5 h, carbon layer 5–6.5 nm) effectively suppresses SEI regeneration, uniformly disperses stress, and maintains electronic continuity, while the carbon layer still retains relatively reversible Li₂. + The diffusion channels significantly improve first-efficiency and cycle retention; however, when the carbon layer is too thick (>6.5 nm), although side reactions are reduced and first-efficiency is further improved, the thicker carbon film increases Li content. + Diffusion resistance leads to limitations in rate performance (6C retention is slightly lower than in Example 1). Therefore, carbon coating exhibits a typical pattern of "too thin and it fails—moderate is optimal—too thick and it is limited," with the optimal thickness range formed during 4-hour deposition, achieving a balance between suppressing side reactions and ensuring kinetics.

[0109] Table 6

[0110] Comparing Example 1 and Comparative Examples 1 and 2 in Table 6, it can be seen that Comparative Example 1, lacking phenolic resin, suffers from insufficient carbon skeleton cross-linking, poor pore structure, and low mechanical strength, leading to easy collapse during cycling, exacerbated side reactions, and a significant decrease in first-efficiency and cycling performance. Comparative Example 2, lacking a pore-forming agent, cannot form abundant micropores and lacks nitrogen doping, resulting in insufficient interfacial lithiophilicity and an unstable SEI film, similarly leading to deterioration in rate and cycling performance. The comparison demonstrates that phenolic resin ensures skeleton strength and uniformity, while the pore-forming agent determines porosity and nitrogen doping; only through their synergy can excellent electrochemical performance be achieved.

[0111] In summary, this invention achieves synergistic control of pore structure, framework strength, surface chemistry, and interfacial stability by introducing urea for pore creation and nitrogen doping into a phenolic resin and coal tar pitch composite carbon framework, combined with multi-level structural optimization strategies such as KOH activation, silane deposition, and controllable carbon coating. This method ensures both a high specific surface area and suitable pore volume to promote rapid lithium-ion transport, while maintaining excellent framework compressive strength to mitigate silicon volume expansion. Simultaneously, nitrogen doping enhances the wettability of the electrode and electrolyte and interfacial stability, and the carbon coating effectively suppresses side reactions and improves conductivity. Therefore, the material exhibits significant advantages in first-cycle efficiency, rate performance, and long-cycle stability.

[0112] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structure made using the contents of the present invention specification and drawings, or directly or indirectly applied to other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A phenolic-coal tar nitrogen-doped composite silicon-carbon anode material, characterized in that: The silicon-carbon anode material includes: Composite carbon framework: phenolic resin and coal tar pitch in a mass ratio of 2:1–1:4, with micropores of 0.7–2.0 nm accounting for ≥78%, specific surface area ≥1600 m² / g, and total pore volume ≥0.6 cm³. 3 / g, the composite carbon framework has a mass fraction of 30%–55wt% in the silicon-carbon anode material, and its surface nitrogen content is 0.2–0.6at%; Deposited phase: The deposited phase is vapor-deposited nano-silicon deposited on the surface of the composite carbon framework; the mass fraction of this vapor-deposited nano-silicon in the silicon-carbon anode material is 35%–60wt%; this vapor-deposited nano-silicon is an amorphous silicon phase; when X-ray powder diffraction test is performed using Cu-Kα rays, no obvious crystalline silicon diffraction peaks are observed in the diffraction angle range of 2θ = 28–56°. Among them, obvious crystalline silicon diffraction peaks refer to crystalline diffraction peaks with an aspect ratio greater than 3. Carbon coating: The carbon coating is applied to the surface of the deposited phase; the thickness of the carbon coating is 2–8 nm, and the mass fraction of the carbon coating in the silicon-carbon anode material is 1.0–5.5 wt%.

2. The phenolic-coal tar nitrogen-doped composite silicon-carbon anode material according to claim 1, characterized in that: The compressive strength of the silicon-carbon anode material satisfies the following condition: σ = 28.6 × P + 72.0, where σ is the compressive strength in MPa; P is the mass fraction of phenolic resin in the composite carbon skeleton, ranging from 0.20 to 0.

67.

3. A method for preparing the phenolic-coal tar nitrogen-doped composite silicon-carbon anode material as described in claim 1 or 2, characterized in that: The preparation method includes the following steps: S1. Phenolic resin and coal tar pitch are blended and granulated, and a pore-forming agent is added to obtain a composite precursor; S2. The composite precursor was activated with KOH and acid-washed to obtain a composite carbon framework; S3. The composite carbon framework is sequentially subjected to silane deposition and carbon source coating in a fluidized bed reactor; The pore-forming agent in S1 is 2–6 wt% of the total mass of phenolic resin and coal tar pitch; The activation conditions for KOH in S2 are: KOH to composite precursor mass ratio of 1:1–4:1, temperature of 700–1000℃, and time of 3–6 h. In step S3, the obtained composite carbon framework is heated to a first reaction temperature of 450–600°C under a protective atmosphere, and then silane gas is introduced for vapor deposition at a flow rate of 15 L / min–35 L / min for a deposition time of 5–15 h. After deposition, the temperature is raised to a second reaction temperature of 500–700°C, and then olefin gas is introduced for carbon source coating at a flow rate of 2 L / min–10 L / min for a coating time of 2–6 h.

4. The preparation method according to claim 3, characterized in that: The pore-forming agent in S1 is at least one of NH4Cl, urea, melamine, and polydopamine; The protective atmosphere in S3 is at least one of nitrogen and argon, the silane gas is at least one of silane, silane and propane, and the olefin gas is at least one of acetylene, propylene, methane and ethylene.

5. The preparation method according to claim 3, characterized in that: The compaction density of the silicon-carbon anode material is 0.7–1.5 g / cm³. 3 .

6. The preparation method according to claim 3, characterized in that: The silicon-carbon anode material has a compaction density of 1.1 g / cm³. 3 The resistivity of the powder is <4.5Ω·cm.

7. The preparation method according to claim 3, characterized in that: The tap density of the silicon-carbon anode material is 0.7–1.2 g / cm³. 3 .

8. The preparation method according to claim 3, characterized in that: The silicon-carbon anode material has a D50 of 4–13 μm and meets the following conditions. .

9. A negative electrode sheet, characterized in that: It includes a negative electrode current collector and a negative electrode coating coated on at least one side of the negative electrode current collector, said negative electrode coating comprising the silicon-carbon negative electrode material as described in any one of claims 1 to 2.

10. A lithium-ion battery, characterized in that: The lithium-ion battery includes the negative electrode sheet as described in claim 9; the lithium-ion battery is any one of a liquid lithium-ion battery, a semi-solid lithium-ion battery, and an all-solid lithium-ion battery.

Citation Information

Patent Citations

  • Carbon-coated silicon-carbon composite material as well as preparation method and application thereof

    CN116885126A

  • Silicon-carbon negative electrode material for lithium-ion battery and preparation method thereof

    CN118156450B

  • Porous silicon carbon negative electrode material and preparation method and application thereof

    CN119324206A